2015
DOI: 10.1186/s13756-015-0042-y
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene and aseptic techniques during routine anesthetic care - observations in the operating room

Abstract: BackgroundMore knowledge is needed about task intensity in relation to hand hygiene in the operating room during anesthetic care in order to choose effective improvement strategies. The aim of this study was to explore the indications and occurrence of hand hygiene opportunities and the adherence to hand hygiene guidelines during routine anesthetic care in the operating room.MethodsStructured observational data on hand hygiene during anesthetic care during 94 surgical procedures was collected using the World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 60 publications
(74 reference statements)
4
31
1
1
Order By: Relevance
“…Nevertheless, the number of HHOs completed in this study is consistent with data reported for anesthesiologists in other studies. [6][7][8] Third, most participants remarked that, by following the ''five moments'' prescription, they used alcohol hand gel more frequently than they typically would in their usual practice. It follows that positive breathalyzer tests may be less likely than our data suggest when anesthesiologists invoke their usual hand hygiene habits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the number of HHOs completed in this study is consistent with data reported for anesthesiologists in other studies. [6][7][8] Third, most participants remarked that, by following the ''five moments'' prescription, they used alcohol hand gel more frequently than they typically would in their usual practice. It follows that positive breathalyzer tests may be less likely than our data suggest when anesthesiologists invoke their usual hand hygiene habits.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The feasibility of applying this standard when administering an anesthetic has been challenged. [6][7][8] Compliance is frequently poor in anesthetic environments, even if convenient alcohol hand gel preparations are used. [6][7][8][9][10] Nevertheless, it is the policy of hospital administrators and the Health Quality & Safety Commission New Zealand that all healthcare workers comply with the five moments approach.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing surgical procedures are exposed to multiple risks for HAIs during the use or insertion of invasive medical devices, and these risks increase with poor hand hygiene practices 5 . Previously, we carried out a study in the OR that showed alarmingly low (5.3%) adherence to hand hygiene guidelines 6 . This motivated us to carry out the present study.…”
Section: Purpose and Research Questionmentioning
confidence: 99%
“…[12][13][14][15] Preventive innovations such as the correct timing, type and dose of prophylactic antibiotics have in many cases been reported to be suboptimal. [16][17][18][19] In addition, ample evidence exists for deficits in hand hygiene during anesthetic care, [20][21][22][23][24] intraoperative patient warming during surgery, [19] and restricted traffic flow during surgical procedures. [25][26][27][28] These results show a substantial "knowdo gap" [29] between what is known about safe and effective practice and what is actually done in the OR, supporting an urgent need for implementing evidence-based practice for preventive innovations in order to enhance the safety of patients.…”
Section: Introductionmentioning
confidence: 99%